2018
DOI: 10.3389/fphar.2018.00303
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin Oxidation Products and Cerebral Vasoconstriction

Abstract: Key evidence in support of the hypothesis that bilirubin oxidation products (BOXes) contribute to the vasoconstriction associated with subarachnoid hemorrhage (SAH) are the (1) presence of BOXes in cerebral spinal fluid from SAH patients and (2) ability of one or more BOXes to elicit vasoconstriction. We critically evaluate this key evidence, detail where gaps remain, and describe recent approaches that will address these gaps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…On the other hand, previous studies have demonstrated that the mTOR signaling pathway plays a vital role in cerebral vasospasm following SAH ( 243 ). The increased levels of mTOR, P70S6K1, and 4E-BP1 ( 167 ) in basilar arteries were significantly associated with SAH and potentially mediated the activation of cerebral vasospasm. As a member of the PI3K family, mTOR orchestrates the phosphorylation of key downstream proteins P70S6K1 and 4E-BP1, both of which promote the proliferation of key vasculature wall cells ( 168 ).…”
Section: Immune Inflammation Relevant Signaling Pathways In Sahmentioning
confidence: 98%
“…On the other hand, previous studies have demonstrated that the mTOR signaling pathway plays a vital role in cerebral vasospasm following SAH ( 243 ). The increased levels of mTOR, P70S6K1, and 4E-BP1 ( 167 ) in basilar arteries were significantly associated with SAH and potentially mediated the activation of cerebral vasospasm. As a member of the PI3K family, mTOR orchestrates the phosphorylation of key downstream proteins P70S6K1 and 4E-BP1, both of which promote the proliferation of key vasculature wall cells ( 168 ).…”
Section: Immune Inflammation Relevant Signaling Pathways In Sahmentioning
confidence: 98%
“…Finally, aSAH patients with DCI have increased levels of bilirubin oxidation products (BOXs) compared to patients without DCI (Pyne-Geithman et al, 2013). This difference is mainly dependent on levels of oxidative products in the CSF (Pyne-Geithman et al, 2013;Rapoport, 2018;Peeyush Kumar et al, 2019). Similar to free Hb, BOXs inhibit endothelial NO synthesis (Peeyush Kumar et al, 2019).…”
Section: Phase Ii: Oxidative Stressmentioning
confidence: 99%
“…Red blood cells in the subarachnoid space are hemolyzed, releasing hemoglobin, bilirubin and oxygen free radicals. These toxic molecules induce increased expression of endothelin-1 and reduced levels of nitrous oxide, leading to endothelial cell dysfunction and VSP 6 8 . Although angiographic VSP eventually resolves, arterial fibrosis, endothelial thickening and reduced arterial compliance may persist over time and contribute to the poor clinical outcomes observed in patients with DCI 9 .…”
Section: Introductionmentioning
confidence: 99%